2015
DOI: 10.1590/1516-635x1704503-510
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-phytate Phosphorus and 1a-Hydroxycholecalciferol on Growth Performance, Bone Mineralization, and Carcass Traits of Broiler Chickens

Abstract: This study evaluated the effects of dietary non-phytate phosphorus (NPP) and 1α-hydroxycholecalciferol (1α-OH-D 3 ) on the growth performance, bone mineralization, and carcass traits of 1-to 21-day-old broiler chickens. On the day of hatch, 600 male Ross 308 chicks were weighed and randomly assigned to 12 treatments, with five cages of 10 birds each. A 6 × 2 factorial arrangement was applied, consisting of 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, or 0.45% NPP and 0 or 5 μg/kg of 1α-OH-D 3 . The basal diet contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Reduced calcium and Nonphytate phosphorus by 10% to 30% of required levels showed no influence on internal organs and carcass attributes of broilers at 7 weeks of age, as per Imari et al (2020), which is consistent with our findings. In agreement with this, Han et al (2015) also observed that dietary levels of 2016) also found that a decreased calcium to Nonphytate phosphorus ratio resulted in reduced broiler carcass production.…”
Section: Carcass Characteristicssupporting
confidence: 64%
“…Reduced calcium and Nonphytate phosphorus by 10% to 30% of required levels showed no influence on internal organs and carcass attributes of broilers at 7 weeks of age, as per Imari et al (2020), which is consistent with our findings. In agreement with this, Han et al (2015) also observed that dietary levels of 2016) also found that a decreased calcium to Nonphytate phosphorus ratio resulted in reduced broiler carcass production.…”
Section: Carcass Characteristicssupporting
confidence: 64%
“…The present study findings are in agreement with published reports in this field. Han et al (2015) reported that nPP levels did not significantly influence the carcase, breast, and legs relative weight. Likewise, Akter et al (2016) pointed out that the relative weight of birds' internal organs were not impacted by reduced Ca and nPP from 10 g/kg Ca and 4 g/kg nPP to 6 g/kg Ca and 3 g/kg nPP.…”
Section: Carcase Traitsmentioning
confidence: 96%
“…(2009) reported that interaction between phytase and 1α-OH-D 3 in diets containing 2.9 g/kg nonphytate phosphorus (NPP) could improve tibia related parameters in broiler chicks, while it could not improve performance parameters. Han et al. (2015) reported that supplementation of 5 μg/kg 1α-OH-D 3 in diets containing 0.30% of NPP could improve growth performance and tibia mineralization of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%